Performance Of Micro Steam Engine - Louis, Mark Selvan Anthony Rogers (Universiti Sains Malaysia, 2017)
Steam engines were the first engine type to see widespread use. It was the foundation of the industrial revolution. This study is done to investigate the performance and specification of the components that make up the Micro Wobbler Steam Engine. The system comprise of 3 parts namely the boiler, the pressure regulating valve and the steam engine. The LPG fired boiler is a vertical fire tube boiler with a 7.5 L capacity and a maximum operating pressure of 10 Bar. The pressure regulating valve is a Yoshitake GD 45P that is compact, lightweight and with a minimum inlet pressure of 2 Bar. The steam engine is Micro Wobbler Steam engine. The performance of the system was determined by varying the inlet pressure and the load while measuring the flowrate and torque. Subsequently, the brake power, indicated power, friction power, brake thermal efficiency and mechanical efficiency were calculated. From the experiment carried out, the highest brake power, indicated power and friction power were 4.35 Watts, 17.4 Watts and 13.05 Watts. The highest indicated thermal efficiency was 0.23% while the mechanical efficiency remained constant at 25%. Whereas the boiler efficiency was 43%. The results indicates a relatively low overall efficiency of the system that is 0.056%.